2019
DOI: 10.1002/ecm.1390
|View full text |Cite
|
Sign up to set email alerts
|

Persistence and turnover in desert plant communities during a 37‐yr period of land use and climate change

Abstract: Understanding long‐term changes in ecological communities during global change is a priority for 21st‐century ecology. Deserts, already at climatic extremes, are of unique interest because they are projected to be ecosystems most responsive to global change. Within a 500‐km2 landscape in the Mojave Desert, USA, we measured perennial plant communities at 100 sites three times (1979, 2008, and 2016) during 37 yr to evaluate six hypotheses of community change. These hypotheses encompassed shifts in community meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 94 publications
1
8
0
Order By: Relevance
“…Alternatively, it is possible that climate had minimal influence in comparison to reduced grazing pressure. Livestock grazing and to some extent feral burros ( Equus asinus ) have been reduced around the study area since the 1990s (Abella et al 2019). With minimal evolutionary history of intensive large‐herbivore grazing, native plant cover and diversity could be expected to increase after grazing ceases.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, it is possible that climate had minimal influence in comparison to reduced grazing pressure. Livestock grazing and to some extent feral burros ( Equus asinus ) have been reduced around the study area since the 1990s (Abella et al 2019). With minimal evolutionary history of intensive large‐herbivore grazing, native plant cover and diversity could be expected to increase after grazing ceases.…”
Section: Discussionmentioning
confidence: 99%
“…(2014) have estimated a decline in net primary productivity of about 1% per decade in the early twenty‐first century due to changing climate. However, near our study area, continuous plant surveying over the past 30+ years suggests increases in plant density and plant cover, possibly due to decreased freezing and a reduction in grazing intensity (Abella et al., 2019). For the locations examined here, we lack direct information on vegetation changes over time but recognize that such changes may be important contributors to changes discussed previously.…”
Section: Discussionmentioning
confidence: 90%
“…The trend for increased abundance of native shrub seedlings in the vertical mulch and microtopography treatments at some sites suggests that at least conditions enabling recruitment opportunities were reinstated. In natural, undisturbed desert ecosystems, pulses of native perennial seedlings can appear relatively frequently among years, but survival of the seedlings across multiple years rarely occurs (Abella et al 2019). Bowers et al (2004), for example, found that on average, only 0.1% of native perennial seedlings lived as long as 4 years in the Sonoran Desert.…”
Section: Discussionmentioning
confidence: 99%